Power and the Role of the Superintendent - Teresa Northern Miller; Trudy A. Salsberry; Mary A. Devin (Educational Considerations, 2009)
As schools move further into the 21st century, there is a strong need for education leaders and those who train them to prepare students for a future that is decidedly different from the past and to do so in a high stakes accountability environment. In meeting these challenges, school superintendents encounter politics in every arena and constantly use a variety of types of power to accomplish their goals.
Keywords: perspective; power; Superintendent; role; analysis; data; transcript